2012
DOI: 10.1590/s0100-72032012000200008
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de uma estratégia para ampliar a adesão ao rastreamento do câncer de mama no Nordeste brasileiro

Abstract: ResumoOBJETIVO: avaliar as ações do Programa "Um Beijo Pela Vida", desenvolvido em um município do Nordeste brasileiro visando ampliar a adesão ao rastreamento do câncer de mama em mulheres cadastradas pela Estratégia Saúde da Família. MÉTODOS: Utilizou-se abordagem quantitativa para avaliar a cobertura das ações de rastreamento nas mulheres com 40 anos de idade ou mais. Foi realizada busca ativa das mulheres por agentes comunitários de saúde das nove Equipes de Saúde da Família do município. Os percentuais da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 8 publications
1
15
0
4
Order By: Relevance
“…Studies have shown errors or ignorance of primary care professionals in regard to the practice and implementation of CBE (20)(21)(22)(23) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown errors or ignorance of primary care professionals in regard to the practice and implementation of CBE (20)(21)(22)(23) .…”
Section: Discussionmentioning
confidence: 99%
“…According to the MOH, for effective actions of the program to control this cancer, it is necessary to fulfill the coverage goals of the target population and adhere to the proper frequency of the exam, in addition to appropriate monitoring of health care users (23) .…”
Section: Discussionmentioning
confidence: 99%
“…Ao ser investigada a cobertura mamográfica em um programa de controle do câncer de mama no interior da Paraíba 32 clínico, e para as mulheres entre 50 e 69 anos, o percentual foi 56,8% 32 . Apesar das diferenças metodológicas, os estudos demonstraram que a população feminina encontra barreiras para realização de forma adequada do controle do câncer de mama.…”
Section: Discussionunclassified
“…These women are at higher risk of being diagnosed in advanced stages, which could result in an increase in the number of deaths registered from this cause (Hofvind et al, 2004;Paci et al, 2004). In Brazil, this situation was already confirmed by Barreto et al (2012), who suggested that the increased mortality rates could be related to the considerable amount of cases diagnosed in advanced stages of cancer. In the same way, Rezende et al (2009) observed that 51% of all breast cancers diagnosed in Rio de Janeiro were in advanced stages of the disease (clinical stages II, III and IV).…”
Section: Discussionmentioning
confidence: 92%